(untitled) (Journal of Multidisciplinary Sciences and Innovations, 2025)
This article addresses the Cauchy problem for first-order linear differential equations with piecewise continuous arguments within the theory of differential equations. The study differs from previous research in this field by considering the nonhomogeneous case, which substantiates the novelty of the results.